2017
DOI: 10.1186/s13000-017-0679-3
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of BRAF and KRAS mutations in Chinese patients with low-grade serous carcinoma of the ovary

Abstract: BackgroundMounting evidence has shown that KRAS and BRAF are somatic mutations associated with low grade serous carcinoma (LGSC) of the ovary. However, the frequency of KRAS or BRAF mutation was variable in literatures, with a frequency of 16–54% for KRAS mutation and 2–33% for BRAF mutation. Meanwhile, the prognostic significance of KRAS or BRAF mutation remains controversial.MethodsCodons 12 and 13 of exon 2 of KRAS gene and exon 15 of BRAF gene were analyzed using direct Sanger sequencing in 32 cases of LGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…Patients with BRAF -mutated SBTs have been shown to present at earlier stages (37). However, no significant differences were found in overall survival or disease-free survival among BRAF -mutated and non-mutated SBTs or LGSCs in some studies (11, 37).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Patients with BRAF -mutated SBTs have been shown to present at earlier stages (37). However, no significant differences were found in overall survival or disease-free survival among BRAF -mutated and non-mutated SBTs or LGSCs in some studies (11, 37).…”
Section: Discussionmentioning
confidence: 87%
“…In our study, V600E BRAF V600E mutations were present in 48% (25/52) of SBTs and 5% (1/22) of all LGSCs. BRAF mutations have been described in up to 48% of SBTs (611). Some studies have reported BRAF mutations in 19-33% of LGSCs (6, 35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cycling conditions were as described previously. [18] After identification by agarose gel electrophoresis, the PCR products were purified with the DNA Clean/Extraction Kit (GeneMark), then submitted to direct sequencing on an ABI 3730xl genetic analyzer (Invitrogen Life Technologies, Carlsbad, CA, USA), and detailed steps were consistent with those reported earlier. [19] The resulting reads were aligned using Chromas software, and all mutations were confirmed in both the sense and anti-sense directions.…”
Section: Methodsmentioning
confidence: 99%
“…PUS1, whose deficiency affects muscle morphology in mice (17), has a z-score of -0.78 in muscle but a FUGUE score of 0.94. KRAS, mutations in which cause ovarian carcinoma (18), has a z-score of -0.12 in ovary and FUGUE score of 0.82. TGF-beta functions in gonadal development (19).…”
Section: Fugue Validation In Independent Datasets and Utility In Mappmentioning
confidence: 99%